Lipopolysaccharide reduces sodium intake and sodium excretion in dehydrated rats - Almeida, Roberto L. de [UNESP]; Constancio, Juliana [UNESP]; Vendramini, Regina Célia [UNESP]; Fracasso, Jose F. [UNESP]; Menani, José Vanderlei [UNESP]; De Luca, Laurival A. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The objective of this study was to find out if lipopolysaccharide (LPS) administered intraperitoneally affects sodium and water intake and renal excretion in dehydrated rats. LPS (0.3-5 mg/kg b.w.) inhibited 0.3 M NaCl intake induced by subcutaneous injection of the diuretic furosemide (FUR. 10 mg/kg b.w.) combined with the angiotensin converting enzyme inhibitor, captopril (CAP, 5 mg/kg b.w.). Only the highest doses of LPS (2.5 and 5 mg/kg) inhibited water intake induced by FURO/CAP. LPS (0.6 mg/kg) reduced urinary volume and sodium excretion, but had no effect on mean arterial pressure or heart rate of rats treated with FURO/CAP. LPS (0.3-5.0 mg/kg) abolished intracellular thirst and reduced by 50% the urine sodium concentration of rats that received 2 ml of 2 M NaCl by gavage. LPS (0.3-5.0 mg/kg) also reduced thirst in rats treated with FURO alone (10 mg/rat sc). The results suggest that LPS has a preferential, but not exclusive, inhibitory effect on sodium intake and on intracellular thirst. The inhibition of hydro-mineral intake and the antinatriuresis caused by LPS in dehydrated rats may contribute to the multiple effects of the endotoxin on fluid and electrolyte balance and be part of the strategy to cope with infections. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: LPS; Sodium appetite; Thirst; Dehydration; Kidney; Sickness behavior